The Impact of Education Programs about Smoking Cigarrete on Junior High School Student Level of Knowledge and Attitudes - Maulana AD, Rahmah (2014)
the conclusion of this study was education about smoking cigarette for students had no impact on the student knowledge but had a positive impact on the student attitude